A Reputation Analysis and State Higher Education Institution Performance in West Sumatra, Indonesia - Bashori, Bashori (Idarah (Jurnal Pendidikan dan Kependidikan), 2022)
Abstract: The reputation of the school is a factor in a student's selection while selecting a higher education facility. The study's goal was to examine West Sumatra's PTKIN and determine its distinctiveness. With a case study methodology, this form of research is qualitative. Data collection methods include observations, documentation, and interviews. Data analysis utilizing the Creswell paradigm involves four steps: collaborative reduction, presentation, and verification. The findings revealed, According to Selnes' view, UIN Imam Bonjol Padang is mostly non-academic and has a good name, a reputation among rivals, is well-known, and is simple to recall. Second, both academic and non-academic reputation grounds are consistent with UIN Bukitinggi's reputation; and Thirdly, by raising the standards of top educational institutions, UIN Mahmud Yunus has established an academic reputation (Excellence Learning Institute). Strength and potential in meeting the demands of educational institutions in the field have an impact on reputational distinctiveness. Abstrak: Salah satu aspek keputusan mahasiswa dalam memilih lembaga pendidikan tinggi adalah reputasi lembaga. Tujuan penelitian adalah untuk menganalisis PTKIN di Sumatera Barat dan melihat distingsinya. Kualitatif menjadi jenis penelitian ini, dengan pendekatan studi kasus (case study). Wawancara, dokumentasi, dan observasi digunakan dalam perolehan data. Proses penganalisisan data menggunakan model Creswell yaitu; kolektif, reduksi, penyajian, dan verifikasi. Hasil penelitian menunjukkan, Pertama, UIN Imam Bonjol Padang secara dominan bereputasi non-akademik sejalan dengan teori Selnes yaitu; reputasi berupa nama baik, reputasi pesaing, dikenal luas, dan mudah diingat; Kedua, UIN Bukitinggi memiliki dua basis reputasi yang sejalan baik akademik dan non-akademik; dan Ketiga UIN Mahmud Yunus secara kelembagaan bereputasi secara akademik melalui peningkatan mutu lembaga pendidikan yang unggul (Excellence Learning Institute). Diferensiasi reputasi dipengaruhi oleh kekuatan dan peluang dalam merespon kebutuhan terhadap dinamika tuntutan dunia industri